From fear to fluency: Examining anxiety in English language learners and strategies to minimize it - Teuku Azhari; Ratri Candrasari; Dini Rizki; Dewi Kumala Sari; M. Nasir (Studies in English Language and Education, 2026)
Language anxiety is a prevalent issue among English language learners (ELLs) and continues to negatively affect their language learning and performance. This study investigated key factors contributing to language anxiety and examined its influence on learners’ fluency and overall English proficiency. The study explored how anxiety manifests in learners and the strategies used to reduce its effects in the classroom. Employing a qualitative phenomenological design, the study was conducted at a university in Indonesia. The population consisted of 138 civil engineering students from four classes, of whom 66 were randomly selected as participants. In addition, four ELT lecturers who teach English on campus participated in this study. Data were collected through semi-structured interviews consisting of 15 guiding questions and analyzed using thematic analysis. The findings indicate that learners experienced heightened anxiety when they were required to speak in front of the class and when anticipating errors. Pronunciation difficulties, fear of peer judgment, and low self-efficacy were identified as the major contributing factors. Anxiety was found to significantly hinder fluency, manifesting in cognitive disruption, slow speech production, and loss of confidence, which often led learners to rely on memorization rather than spontaneous responses. To address these challenges, English language teachers implemented strategies such as pair work, small-group discussions, and positive reinforcement. These practices contributed to a more supportive learning environment and encouraged learner participation. Therefore, teachers should regularly integrate pair work and small-group discussions into their classes, and relevant institutions should offer training in anxiety-reduction strategies.